Implementation of the Principles of Adult Learning to the Tajweed Study Group of Rumah Al-Qur'an Petra Kota Padang - klub Harahap, Mhd Tanwir; Jamaris, Jamaris (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
The background of this research was that the outreach program on manure was not going well because the outreach activities in the implementation of follow-up extension activities experienced obstacles, this was allegedly due to the obstacles encountered by the extension participants of the Cinta Damai Farmer Group. This study aims to look at the farmers' obstacles in implementing the results of manure counseling which includes getting, processing, using and determining the portion of the use of manure. This study uses a quantitative descriptive method. The population in this study were all participants of the Cinta Damai Farmers Group in Cubadak Mentawai Village, East Pariaman. The sampling technique used purposive sampling method. The data collection tool used in this study was a questionnaire. The data collection technique used was a closed questionnaire. Data analysis techniques in this study are data description and data analysis. The results obtained in this study: a) Barriers to farmers in obtaining manure. b) Barriers of farmers in processing manure. c) Barriers of farmers in the use of fertilizers. d) Barriers to farmers in determining the dosage of fertilizer use.Keywords : Barriers, Agricultural Products